Marketization of universities in China: A critical discourse analysis of the university president's message. Issue 5 (October 2019) - Teo, Peter; Ren, Songsha
This article focuses on the global phenomenon of the marketization of higher education and how it has shaped the discourses of China's top universities. By analyzing the university presidents' messages published in the websites of 36 top-ranked universities in China, the aim is to ascertain the extent to which this institutionalized genre imbricates a marketizing role with other ideological imperatives. Informed by the theoretical principles of Critical Discourse Analysis and adopting a genre analysis methodological approach, we first examined the macro-level rhetorical structure followed by a micro-level analysis of the discursive strategies used in the presidents' messages. The findings reveal a dynamic interweaving of three distinct discursive strands – bureaucratic, conversational and advertising – constructed in and around the move structure of the presidents' messages. This interdiscursive analysis reveals competing imperatives and contestations that reflect the dual role of the presidents' messages to project a globalized, international outlook while maintaining an allegiance to political ideologies and national interests that top-ranked universities in China have to simultaneously negotiate.